Body mass index and prostate cancer risk in the Carotene and Retinol Efficacy Trial. Issue 3 (May 2019) - Bonn, Stephanie E.; Barnett, Matt J.; Thornquist, Mark; Goodman, Gary; Neuhouser, Marian L.
Abstract : The aim of this study was to investigate the association between BMI (kg/m 2 ) and prostate cancer risk. BMI is a modifiable lifestyle factor and may provide a unique opportunity for primary prevention of prostate cancer if a causal association exists. Data from 11 886 men from the Carotene and Retinol Efficacy Trial (CARET, 1985–1996 with active follow-up through 2005) comprising current and former heavy smokers were analyzed. CARET was a multicenter randomized, double-blind placebo-controlled chemoprevention trial testing daily supplementation of 30 mg β-carotene+25 000 IU retinyl palmitate for primary prevention of lung cancer. Prostate cancer was a secondary outcome. Nonaggressive disease was defined as Gleason less than 7 and stage I/II. Aggressive disease was primarily defined as at least Gleason 7 or stage III/IV, and secondarily by excluding Gleason 3+4 from the first definition. BMI was calculated from measured weight and height. Cox proportional hazards regression models were used to estimate hazard ratios (HRs) with 95% confidence intervals (CIs) for cancer incidence between BMI categories. During follow-up, 883 men were diagnosed with prostate cancer. In the analysis of aggressive disease when Gleason 3+4 was excluded, men with a BMI of at least 35 kg/m 2 had an increased rate of prostate cancer (HR: 1.80, 95% CI: 1.04–3.11, P trend =0.04) compared with men with BMI 18–24.9 kg/m 2 . No other differences were seen in risk estimates for overall, nonaggressive or aggressive prostate cancer including all Gleason 7 cases, between BMI categories. Our results show an association between having a BMI of at least 35 kg/m 2 and an increased risk of aggressive prostate cancer (not including Gleason 3+4 tumors), but do not support an association between BMI and risk of overall, aggressive disease including all Gleason 7, or nonaggressive prostate cancer within a population of current and former heavy smokers.